Investigations of clamping and climbing mechanisms for the design of semi autonomous areca palm climber - SUPRITHA; Er. Shivaji K.P (Guide) (Tavanur 2017 Kelappaji College of Agricultural Engineering and Technology)
Investigations of clamping and climbing mechanisms for the design of semi autonomous areca palm climber
Investigations of clamping and climbing mechanisms for the design of semi autonomous areca palm climber